Exploring Pre-Service Teachers’ Readiness through Internship Program Completion - Repi, Henny Yulia; Merie, Merie Agustiani; Nurul, Nurul Afifah; Nurhasanah, Nurhasanah; Dita, Dita Qatrunnada (STKIPM PRESS, 2025)
University students in the education faculty are obliged to enroll in a teaching practice program as pre-service teachers in order to improve their teaching competences. The purpose of this study was to find out how prepared pre-service teachers felt about completing their internship. 97 students of Baturaja University's Teacher Education Faculty, South Sumatera Province, who have completed microteaching and internship programs were involved as the population in this quantitative study, and 42 students were the sample of the study who voluntarily answered the researchers' questionnaire. The study employed a questionnaire consisting of eighteen items, which were categorized into four teaching competencies as indicators and assessed using the Linkert scale. These competencies included social, professional, educational, and personality. The result showed that the pre-service teachers from the Faculty of Teacher Training at Baturaja University exhibited a good level of teaching readiness (M=3.21). Furthermore, for each competence, the result showed that no pre-service teachers were in the poor category in each competence. There were more than 80% of pre-service teachers in the excellent and good categories. The rest, less than 20% of them, were in the average category. From the research findings, we can conclude that internship program was very essential for pre-service teachers’ readiness.